MOTIVASI MAHASISWA PADA MATA KULIAH KIMIA DASAR 2 MENGGUNAKAN TEKS BAHASA INGGRIS - Wiwin Puspita Hadi (Universitas Islam Balitar, 2017)
The objective of this study is to see students ’ motivation to use English text teaching materials of Basic Chemistry 2. This study used descriptive design employing rate parcentage and descritive statistcs to analyze data. Sample of the study was students joining in the Basic Chemistry course at Trunojoyo Unuversity Madura. Data were collected using quetsionnairee and analyzed using descriptive statistics. The findings of the study were 43% students agreed to use English teaxt teaching materials to learn Basic Chemistry course. Students assured to suggest that English teaching materials encouraged students to learn more and searched other similar teaching materials to enrich the mastery and understanding.